Humanitarian aid under sanctions: From the problem statement to the search for solutions - L. D. Oganisyan L.D. (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the context of a sharp aggravation of interstate rivalry, an increase in natural disasters and the emergence of new epidemiological challenges, the problem of timely provision of humanitarian assistance to the population of the most affected countries and regions becomes especially acute. Its solution, already fraught with a whole complex of objective economic, political and other difficulties, is further complicated by the existing practice of imposing unilateral and multilateral or international sanctions, which have become one of the key instruments of the leading subjects of world politics. And although formally sanctions regimes are provided with humanitarian exceptions designed to minimize their negative consequences for the population of target countries, their imposition inevitably results in new obstacles to the provision of humanitarian assistance to those in need. The paper identifies the key challenges associated with provision of humanitarian aid under the existing sanctions restrictions, and assesses the prospects for addressing them in the contemporary context. The first section examines political and academic debates on the negative humanitarian consequences of sanctions and possible ways to overcome them. In particular, the author identifies the logic behind the transition from comprehensive to ‘smart’ sanctions, as well as the specifics of applying humanitarian exceptions. The second section outlines key aspects of the complex disruptive impact of restrictions on humanitarian assistance, including the technical and political barriers faced in the implementation of humanitarian exceptions. Finally, the third section identifies current trends in the use of humanitarian exceptions by the main initiators of restrictive measures. In this context, particular attention is paid to the UN Security Council Resolution 2664, adopted in December 2022, which mandates the inclusion of standardized exemptions in UN sanctions regimes in order to minimize the impact of restrictive measures on the provision of assistance and to alleviate the suffering of those in need. The author concludes that although there still remain possibilities to address the negative humanitarian consequences of sanctions, this requires strong political will on the part of the international community.